Clinical cases and pearls in medicine - Sainani, G. S. (Jaypee Brothers Medical Publishers (P) Ltd., 2015)
This book has been written with an aim to facilitate students preparing for medicine practical at final MBBS, MD, DNB, FCPS and MRCP examinations. The author discusses 203 clinical cases and 101 pearls in medicine. Pearls are nothing but important messages of clinical medicine which will help students to face the viva voce during practical examination. Each clinical case covers all important aspects of the case which the student is expected to know for practical. The book is enforced with 309 illustrations (relevant sketch diagrams and clinical photographs of the patients). Every important case is followed by the relevant viva voce.-- Source other than Library of Congress.